2012
DOI: 10.1186/1471-2407-12-119
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of anti-p53 and anti-KRas circulating antibodies in esophageal cancer patients treated with chemoradiotherapy

Abstract: BackgroundP53 mutations are an adverse prognostic factor in esophageal cancer. P53 and KRas mutations are involved in chemo-radioresistance. Circulating anti-p53 or anti-KRas antibodies are associated with gene mutations. We studied whether anti-p53 or anti-KRas auto-antibodies were prognostic factors for response to chemoradiotherapy (CRT) or survival in esophageal carcinoma.MethodsSerum p53 and KRas antibodies (abs) were measured using an ELISA method in 97 consecutive patients treated at Saint Louis Univers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…There are many factors that may be prognostic for overall survival in esophageal cancer. Tumor grade, growth patterns, sex, molecular markers, and stage are among a few that are believed to be important . The nodal status at the time of diagnosis can be particularly significant for determining treatment strategy, as well as prognosticating survival .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many factors that may be prognostic for overall survival in esophageal cancer. Tumor grade, growth patterns, sex, molecular markers, and stage are among a few that are believed to be important . The nodal status at the time of diagnosis can be particularly significant for determining treatment strategy, as well as prognosticating survival .…”
Section: Introductionmentioning
confidence: 99%
“…Tumor grade, growth patterns, sex, molecular markers, and stage are among a few that are believed to be important. [2][3][4][5][6] The nodal status at the time of diagnosis can be particularly significant for determining treatment strategy, as well as prognosticating survival. 7,8 However, the currently utilized methods to evaluate nodal status are limited by their accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Although there was not enough evidence of s‐p53 Abs in esophageal adenocarcinoma, a few papers have shown that s‐p53 Abs seem to be useful in detecting esophageal adenocarcinoma with p53 overexpression …”
Section: S‐p53 Abs In Patients With Esophageal Squamous Cell Carcinomamentioning
confidence: 99%
“…However, median OS is a snapshot comparison of a single time point and thus provides a limited measure of benefit. In particular, differences in the durability of survival, i.e., information on those patients that may survive longer than the median value, are not conveyed 56 , 57 . Additionally, log-rank tests are used to determine if the difference observed between 2 survival curves at a certain time point is statistically significant.…”
Section: Is There a Need To Redefine Treatment Goals?mentioning
confidence: 99%